Polimorfisme Gen DRD2 rs1799732 (-141c) Terhadap Terapi Aripiprazole pada Pasien Skizofrenia: Polymorphism Gene DRD2 rs1799732 (-141c) Against Aripiprazole Therapy In Schizophrenia Patients - Fitri Fitri; Irsan Saleh; Theodorus Theodorus (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
The polymorphism rs1799732 (-141C) is located in the 5 'promoter region of DRD2, where these SNPs can influence modulation of transcription activity and D2 receptor density. This study aims to provide a literature review of the polymorphism rs1799732 (-141C) because this gene polymorphism is the most common gene polymorphism in the world related to schizophrenia. This gene polymorphism is known to play a role in the variability of response to aripiprazole antipsychotic therapy in schizophrenic patients. The type of review used in this article is in the form of a literature review of 38 literature from various journals and textbooks. Schizophrenia is a disease that can affect the brain. In the brain there is a chemical delivery of messages that will forward messages around the brain. In schizophrenic patients, dopamine is excessive, while dopamine levels play an important role in feelings of pleasure and experiences of different moods. If dopamine levels are imbalanced, sufferers can experience both positive and negative symptoms. The hypothesis states that excessive dopaminergic activity can lead to schizophrenia. The dopaminergic system plays an important role as a modulator of affective and cognitive functions. Dopamine D2 receptor polymorphism is known to be a risk factor for schizophrenia. Polymorphisms are determinants of clinical symptoms and can play a role in the effectiveness and side effects of antipsychotics, including aripiprazole. Aripiprazole is a second-generation antipsychotic, an antipsychotic with partial agonist activity against dopamine D2.